Understanding the resident group - Ruth Emond (Scottish Journal of Residential Child Care)
Residential care has long been considered the poor cousin of case work (Ward, 1997). The low morale of residential workers and their sense of isolation from child care policy and practice developments have been well documented (Berridge & Brodie, 1998, Murray & Hill, 1991). Over recent times there has been a move to raise the profile of such practitioners and to identify the complex and skilled role that they perform in the lives of the young people in their care. In many ways this has focused on the work undertaken with the individual young person. Both the inspection process (in terms of identifying care plans, work with individuals and families) and the research approach taken have compounded such a perspective. As a result there has been a lack of information about how staff work with young people as a group, living together and sharing day to day experiences. More noticeably, there is a general lack of understanding as to the way in which the group functions and the meanings such groups may have for young people living in residential care.